Die Provinztempel Ägyptens von der 0. bis zur 11. Dynastie : Archäologie und Geschichte einer gesellschaftlichen Institution zwischen Residenz und Provinz - Bussmann, Richard. (Probleme der Ägyptologie, 2010)
Egyptian temples are commonly perceived as monumental buildings and royal institutions. However, this perception is true only for the temples of the later periods of dynastic Egypt. Using archaeological and inscriptional data this book explores the social history of the rarely studied local temples from Dynasty 0 to 11 (ca. 3000-2000 BC). A major focus is placed on the investigation of the temple votives, especially those from Hierakonpolis and Abydos. They are one of the most complex sources for the history of the temples between the provincial milieu and the kings. The book shows how these temples develop from locally based institutions to royal ones and how this overall process was embedded in the local history of each site. "...this is an important book for the early history of Egypt, opening new thoughts for the discussion of the interaction between local traditions and state control." Stan Hendrickx